PENGARUH APLIKASI MANAJEMEN LAPORAN KEUANGAN MASJID BERBASIS INFORMATION OF TEKNOLOGI BERBASIS CLOUD TERHADAP PENERAPAN MUAMALAH SYARIAH - Wirawan (Al Qadhi, 2023)
Management of mosque finances is an essential aspect because the mosque is a social institution responsible for managing the community's funds. An Information Technology (IT) cloud-based application for managing mosque financial reports can be a solution to enhance the effectiveness and efficiency of financial management in mosques. This application has several advantages, including ease of. use, accessibility from anywhere, and ensured security features. This research aims to analyze the impact of IT cloud-based mosque financial report management applications on the implementation of Sharia-compliant transactions (muamalah) in mosques. The study employs a quantitative method using a survey approach. The research sample comprises mosque administrators managing mosque finances using IT cloud-based financial report management applications. Data is collected through questionnaires. The research findings indicate that the IT cloud-based mosque financial report management application significantly and positively influences the implementation of Sharia-compliant transactions in mosques. This suggests that the application can assist mosque administrators in applying Sharia-compliant principles in mosque financial management.